Chemical compounds of esential oils from Xyloselinum vietnamense Pimenov & Kljuykov and Xyloselinum leonidii Pimenov & Kljuykov in Vietnam - Thai, Tran Huy; Khang, Nguyen Sy; The, Pham Van; Hien, Nguyen Thi; Hoi, Tran Minh; Thinh, Nguyen Duc; An, Tran Thanh; Minh, Do Thi; Hanh, Nguyen Phuong; Thu Ha, Chu Thi; et al. (Academia Journal of Biology, 2013)
Xyloselinum Pimenov & Kljuykov, an edemic genus for Vietnam, consisting of two species, namely Xyloselinum vietnamense Pimenov & Kljuykov and Xyloselinum leonidii Pimenov & Kljuykov. X. vietnamense is a perennial shrub, 1.0-1.5 m tall; leaves are alternate, tripinnate. X. leonidii is also a perennial shrub, 0.8-1.8 m tall; leaves are alternate, tripinnate. Materials for study of X. vietnamense and X. leonidii were collected in Bat Dai Son Nature Reserve, Quan Ba district and Sinh Lung commune, Dong Van district, Ha Giang province. The essential oil yields from leaves and roots of X. vietnamense were different, viz. 0.16% in leaves and 0.6% in roots (by air-dry material). Main compounds of essential oil from leaves of X. vietnamense were dominated by sabinene (75.0%), santalone (5,1%), γ-terpinene (2.5%). Main compounds of essential oil from roots of X. vietnamense were sabinen (36.5%), terpinene-4-ol (10.3%), Z-β-ocimene (9.7%). The essential oil yields from leaves and roots of X. leonidii were 0.15% and 0.7% respectively (by air-dry material). Main compounds of essential oil from leaves of X. leonidii were sabinene (29.3%), β-phellandrene (17.8%), myrcene (12.9%), α-pinene (7.6%). Main compounds of essential oil from roots of X. leonidii were β-pinene (13.7%), Z-β-ocimene (12.9%), sabinene (10,0%) and β-thujene (9.5%).